2023
DOI: 10.1002/jcp.31038
|View full text |Cite
|
Sign up to set email alerts
|

Hyperuricemia promotes the progression of atherosclerosis by activating endothelial cell pyroptosis via the ROS/NLRP3 pathway

Bin He,
Qiangqiang Nie,
Feng Wang
et al.

Abstract: Hyperuricemia closely correlates with the development of atherosclerosis, but little is known of the mechanism by which atherosclerosis progression occurs in hyperuricemia. Atherosclerosis appears to involve pyroptosis, an emerging mechanism of proinflammatory regulated cell death. This study tested the hypothesis that pyroptosis underlies the relationship between hyperuricemia and atherosclerosis, using ApoE−/− mice (a model of atherosclerosis), human umbilical vein endothelial cells (HUVECs), and human ather… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Regarding the possible mechanism, hyperuricemia significantly promotes the development of atherosclerotic plaques, downregulates the protein levels of inflammatory genes involved in signaling pathway, promotes the formation of foam cells, and increases lipid peroxidation in macrophages treated with oxidized LDL [ 18 , 19 ]. A previous study also indicated that UA levels are positively associated with inflammatory cytokines, such as interleukin (IL)-6, IL-1β, C-reactive protein, and tumor necrosis factor, and may subsequently induce metabolic abnormalities [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the possible mechanism, hyperuricemia significantly promotes the development of atherosclerotic plaques, downregulates the protein levels of inflammatory genes involved in signaling pathway, promotes the formation of foam cells, and increases lipid peroxidation in macrophages treated with oxidized LDL [ 18 , 19 ]. A previous study also indicated that UA levels are positively associated with inflammatory cytokines, such as interleukin (IL)-6, IL-1β, C-reactive protein, and tumor necrosis factor, and may subsequently induce metabolic abnormalities [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endothelial dysfunction, oxidative stress, inflammation, and activation of the renin-angiotensin-aldosterone system have been proposed as potential mechanisms underlying the cardiovascular effects of HU [15]. HU can exacerbate endothelial cell pyroptosis within aortic atherosclerotic plaques, advancing the progression of atherosclerosis [16]. Furthermore, elevated levels of soluble UA can initiate the activation of the NLRP3 inflammasome [17], leading to endothelial cell pyroptosis, a process modulated by cellular ROS levels.…”
Section: Association With Health Risksmentioning
confidence: 99%
“…Moreover, in an angiotensin-II-induced hypertension mouse model, the NLRP3 -/- group had reduced blood pressure and largely recovered endothelial function and oxidative stress markers [ 26 ]. Additionally, hyperuricemia, a known risk factor of atherosclerotic cardiovascular disease, may promote atheroprone actions through the NLRP3 inflammasome-mediated endothelial cell pyroptosis [ 27 ].…”
Section: Inflammasomes In Atherosclerosismentioning
confidence: 99%